Grinding of Agrium phosphate ores in a 3' diameter pilot SAG mill - John Starkey; Rene Cane; Richard May; V. I. Lakshmanan (Canadian Institute of Mining, Metallurgy and Petroleum, 2002)
"The Agrium Kapuskasing Phosphate Operation mines and processes up to 6,000 t/d of phosphate ore. Run-of-mine crushing to minus 6 inches is done in a toothed roll-crusher, while grinding is done in a SAG/ball mill circuit with no coarse recycle classification of the SAG mill discharge. The primary grinding mill is an 18 ft. diameter x 9 ft. EGL, 1500 HP variable speed SAG mill and the secondary mill is a 13 ft. diameter x 21 ft. long, 2000 HP fixed speed, ball mill. When hard ore was treated, the SAG mill restricted the tonnage that could be ground. When soft ore was treated, the ball mill and spiral classifier overloaded and restricted throughput.Recommendations from a plant benchmark and an ore hardness testing program, on how to better utilize installed energy in the Agrium SAG mill when treating soft ore, and how to obtain best results when treating hard ore, were checked in a pilot plant investigation in the 3 ft. diameter Starkey-PRO Pilot SAG Mill. Correlation between the ore hardness testing and the results from the 3’ Pilot SAG mill was very good. In addition, the work indicated the results that could be expected for the different ore types when using either smaller SAG discharge grates and/or a vibrating screen with 10 mesh square opening cloth.INTRODUCTIONAgrium Kapuskasing Phosphate Operation consists of a 6800 t/d open pit mine and a concentrator, near the Town of Kapuskasing in Northern Ontario. The two major ore types are sandy ore and cemented ore. Sandy ore is fine, soft and easy to grind in the SAG mill while cemented ore is harder, more blocky and difficult to grind in the SAG mill. The ratio of sandy to cemented ore in the deposit is thought to be in the order of 80:20 but can range as high as 5050, so it was important for the grinding circuit to have the ability to treat sandy ore alone."